1994
DOI: 10.1128/mcb.14.12.8096
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of double-strand breaks into the genome of mouse cells by expression of a rare-cutting endonuclease.

Abstract: To maintain genomic integrity, double-strand breaks (DSBs) in chromosomal DNA must be repaired. In mammalian systems, the analysis of the repair of chromosomal DSBs has been limited by the inability to introduce well-defined DSBs in genomic DNA. In this study, we created specific DSBs in mouse chromosomes for the first time, using an expression system for a rare-cutting endonuclease, I-Scel. A genetic assay has been devised to monitor the repair of DSBs, whereby cleavage sites for I-Scel have been integrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
553
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 683 publications
(566 citation statements)
references
References 59 publications
9
553
1
2
Order By: Relevance
“…[7][8][9][10] Substantial increases have been obtained by engineering double-strand breaks (DSBs) in the target locus, but this approach is not currently applicable to single-step targeting strategies. [11][12][13][14] Recent approaches to the problem have included the use of short fragments of DNA, 15 DNA/RNA oligonucleotides (reviewed in Ref. 16), modified selection conditions 17 and adeno-associated virus vectors 18 and these have generated some dramatically improved targeting efficiencies.…”
Section: Correspondence: Acg Porter This Paper Is Dedicated To the Mementioning
confidence: 99%
“…[7][8][9][10] Substantial increases have been obtained by engineering double-strand breaks (DSBs) in the target locus, but this approach is not currently applicable to single-step targeting strategies. [11][12][13][14] Recent approaches to the problem have included the use of short fragments of DNA, 15 DNA/RNA oligonucleotides (reviewed in Ref. 16), modified selection conditions 17 and adeno-associated virus vectors 18 and these have generated some dramatically improved targeting efficiencies.…”
Section: Correspondence: Acg Porter This Paper Is Dedicated To the Mementioning
confidence: 99%
“…Several recent studies have reported gene-targeting frequencies of 1-18% HR events per 5 mammalian cell when the targeted DSB was introduced by natural or artificial endonucleases [2][3][4][5][6][7][8] . The ability to generate precise modifications of the genome -knockouts, mutations or corrections -within 1 in 100 to 1 in 5 cells presents this methodology as a potentially powerful tool for genetic studies, biotechnology and gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…24 They can induce site-specific DSBs, and thereby stimulate homologous recombination of up to 10 000-fold in cultured cells. 25,26 MGNs were used to induce homologous recombination in a variety of cell types and organisms, including mammalian cells, mice, plants, Drosophila, Escherichia coli and trypanosome. 27,28 MGN-induced DSB can also be repaired by non-homologous end-joining (NHEJ), an error-prone process, which frequently results in micro-insertions or micro-deletions (indels) at the site of the break.…”
Section: Introductionmentioning
confidence: 99%